The biogeographic basis of Ebola-virus disease outbreaks: A model for other zoonotic diseases? - Real-Giménez, Raimundo; Olivero-Anarte, Jesús; Fa, Julia E.; Farfán-Aguilar, Miguel Ángel; Márquez-Moya, Ana Luz; Vargas-Yañez, Juan Mario; Nasi, Robert (My University, 2017)
We first determined the differential role of favorability of environmental conditions and mammalian chorotypes in explaining the presence of the Ebola virus in Africa. We then combined environmental factors and chorotypes using fuzzy logic, which better explained the distribution of Ebola virus. The core area for the virus was associated with human infections of known animal origin, with infections of unknown source detected in areas that are biogeographically more peripheral. Variation in the environmental favorability for disease outbreaks may be monitored using indices of macroclimatic oscillations. This may provide the basis for an early warning system based on the variation in macroclimatic indices and the locations where human contact with multiple animal species tend to occur. We propose to study the biogeography of zoonoses by: 1) determining the potential spatial distribution of these diseases, according to environmental factors and the biogeographic structure of animals linked to the zoonosis cycle; 2) search for relationships between disease outbreaks and global atmospheric oscillations to forecast periods of higher risk of emergence of the infectious diseases.
Keywords: Ébola; Biogeografía; Zoonosis; Ébola; Corotipos; Mamíferos; África